The French revolution of 1830 - Pinkney, David H. (Princeton legacy library., 2019)
"The French Revolution of 1830, also known as the July Revolution, Second French Revolution or Trois Glorieuses in French, saw the overthrow of King Charles X, the French Bourbon monarch, and the ascent of his cousin Louis-Philippe, Duke of Orléans, who himself, after 18 precarious years on the throne, would in turn be overthrown. It marked the shift from one constitutional monarchy, the Bourbon Restoration, to another, the July Monarchy; the transition of power from the House of Bourbon to its cadet branch, the House of Orléans; and the substitution of the principle of popular sovereignty for hereditary right. Supporters of the Bourbon would be called Legitimists, and supporters of Louis Philippe Orléanists."--Wikipedia.